Response of the pineal gland in rats exposed to three different light spectra of short periods - (:unkn) unknown (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2006)
The pineal gland is a part of the photo-endocrine system. Photon energy is important for the function of this system, and affects the level of nocturnal melatonin. In mammals light-induced suppression of melatonin production is dependent on the intensity and wavelength of the light used. We studied the chronic effects of light wavelengths on the pineal gland in rats after exposure to a short photoperiod using 3 different light spectra with the same irradiance. Male Sprague-Dawley rats were used. The animals were divided into 5 groups. They were exposed 8/16 L:D periods in rooms under automatically regulated light and climate. Lee filters were used for the light spectra application. From animals at the age of 6 months blood samples were taken over a week at the third hour of the dark period under dim red light. The pineal glands were processed for electron microscopy. Melatonin levels in the blood were analyzed by ELISA. Melatonin levels were the higher in control group and group 5 (blue light spectra) compared to the others. We demonstrated that blue light spectra have a greater effect on melatonin production in rats.
Keywords: light spectra; pineal gland; melatonin; short photoperiod; SYRIAN-HAMSTER; MELATONIN; ULTRASTRUCTURE; SUPPRESSION; PHOTORECEPTOR; REPRODUCTION; WAVELENGTHS; IRRADIANCE; HUMANS; SYSTEM